Meditation and Madness. Ancient and Contemporary Speculation on Chinese Bird Totem Art - Zhang, Aixin; Zhilong, Yan (Technium Social Sciences Journal, 2022)
By comparing the forms, meanings and connotations of ancient and contemporary bird symbols, I realize that the driving force for writing this article up to now lies in my judgment on the present situation of bird symbol vision field, especially the idea of building a bridge between the conceptual world and the bird image world. I think the problem is not that ideas are dispensable to human beings, but that bird symbols of different forms and rhythms have invaded the structure of the world of ideas crazily. The so-called contemporary bird symbol has completely succumbed to the charm of discourse, which is a very bad situation for bird images. They often become a specific tool to convey a certain language. Therefore, it is an urgent task for today’s art to restore the concept of prehistoric bird totem’s visual sense and preserve its general inspiration. By integrating the thoughts of Socrates, the founder of Mania, and Foucault, a modernist philosopher, the author tries to deeply grasp the relationship between deep thinking mania and the meaning behind prehistoric bird totem art in the study of bird totem art, hoping that this study will help the audience to understand the relevance between ancient and contemporary bird totem art from a theoretical perspective.